2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2017
DOI: 10.1109/cvpr.2017.97
|View full text |Cite
|
Sign up to set email alerts
|

Shading Annotations in the Wild

Abstract: Understanding shading effects in images is critical for a variety of vision and graphics problems, including intrinsic image decomposition, shadow removal, image relighting, and inverse rendering. As is the case with other vision tasks, machine learning is a promising approach to understanding shading-but there is little ground truth shading data available for real-world images. We introduce Shading Annotations in the Wild (SAW), a new large-scale, public dataset of shading annotations in indoor scenes, compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…While several metrics [13,3,18] have been suggested to evaluate IID, it has been observed that none give the full picture [18]. Therefore, we now assemble and extend a set of metrics that covers many requirements of IID algorithms, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While several metrics [13,3,18] have been suggested to evaluate IID, it has been observed that none give the full picture [18]. Therefore, we now assemble and extend a set of metrics that covers many requirements of IID algorithms, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Shading Annotations in the Wild [18] (SAW) extends and complements IIW [3] with partly dense shading annotations by humans, who were asked to classify pixels as belonging to either smooth shadow areas or non-smooth shadow boundaries. It is taken as a semi-dense GT reference to measure the SAW quality of SIID algorithms applied on the SAW dataset.…”
Section: Realistic and Scarcementioning
confidence: 99%
“…We conduct experiments on two datasets of real world scenes, IIW [5] and SAW [6] (using test data unseen during training) and compare our method with several state-ofthe-art intrinsic images algorithms. Additionally, we also evaluate the generalization of our CGI dataset by evaluating it on the MIT Intrinsic Images benchmark [35].…”
Section: Discussionmentioning
confidence: 99%
“…SAW also provides individual point annotations at cast shadow boundaries. As noted in [6], these points are not localized precisely on shadow boundaries, and so we apply a morphological dilation with a radius of 5 pixels to the set of marked points before using them in training. This results in shadow boundary regions.…”
Section: Supervised Lossesmentioning
confidence: 99%
See 1 more Smart Citation